Development of fast-response turn-on phosphorescent probes for biothiols based on ruthenium(ii) complexes. Issue 17 (12th April 2019) - Zheng, Ze-Bao; Cui, Ji-Chun; Han, Yin-Feng; Ge, Yan-Qing; Zuo, Jian; Hao, Wen-Xin
Abstract : A novel 2, 4-dinitrobenzenesulfonyl appended ruthenium(ii ) complex acting as a fast-response "turn on" phosphorescent sensor for biothiols was successfully demonstrated. Abstract : A novel ruthenium(ii ) complex of [Ru(bpy)2 (BIPP-DNBS)](ClO4 )2 (Ru-BIPP-DNBS ) {bpy = 2, 2′-bipyridine, BIPP-DNBS = 4-bromo-2-(1 H -imidazo[4, 5- f ][1, 10]phenanthrolin-2-yl)phenyl 2, 4-dinitrobenzenesulfonate} has been designed and synthesized as a fast-response turn-on phosphorescent probe for the detection of biothiols. The ruthenium(ii ) polypyridine complex was used as a phosphorescence reporter and 2, 4-dinitrobenzenesulfonate (DNBS) was used as both a recognition unit and phosphorescence quencher.Ru-BIPP-DNBS was weakly phosphorescent owing to the effectual photoinduced electron transfer (PET) from the ruthenium(ii ) luminophore to the sensing group DNBS. Upon treatment with biothiols, the 2, 4-dinitrobenzenesulfonyl group ofRu-BIPP-DNBS was cleaved, and the phosphorescence was "turned on", as a result of the formation ofRu-BIPP . The favorable steric interactions between the 1 H -imidazo[4, 5- f ][1, 10]phenanthroline group and ortho -2, 4-dinitrobenzenesulfonate highly ameliorated the response rate ofRu-BIPP-DNBS toward biothiols, resulting in a rapid thiol-induced SN Ar substitution reaction. This probe also exhibited good linearity ranges with detection limits of 0.47 μM for cysteine and 0.27 μM for glutathione. Furthermore, application ofRu-BIPP-DNBS for the imaging of endogenous biothiols in glioma cell samples was successfully demonstrated.